Violence and the rise of centralized states in East Asia - Lewis, Mark Edward 1954- (Cambridge University Press, 2022)
Violence, both physical and nonphysical, is central to any society, but it is a version of the problem that it claims to solve. This Element examines how states in ancient East Asia, from the late Shang through the end of the Han dynasty, wielded violence to create and display authority, and also how their licit violence was entangled in the 'savage' or 'criminal' violence whose suppression justified their power. The East Asian cases are supplemented through citing comparable Western ones. The themes examined include the emergence of the warrior as a human type, the overlap of hunts and combat (and the overlap between treatments of alien species and alien peoples), sacrifice of both alien captives and 'death attendants' from one's own groups, the impact of military specialization and the increased scale of armies, the emergent ideal of self-sacrifice, and the diverse aspects of violence in the regime of law